IMPROVING PSYCHOMOTRICITY COMPONENTS THROUGH LUDIC ACTIVITIES - Andreea - Gabriela Lazăr1 (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The research aimed to improve some components of psychomotricity (static and dynamic balance, general coordination, segmental coordination, ocular-motor coordination) through playful (ludic) activities. The experiment was carried out at the "Stefan cel Mare" Secondary School in Putna, on a number of 13 pupils in the first grade. The research has started from the premise that many specialists believe that by playing, children discover different realities and truths, training their creative and artistic capacities, and through the strategies they use, they always make appeals to cleverness, spontaneity, inventiveness, and boldness. Through the game, the child can practice his various skills and habits, assert himself, respond spontaneously to new motoring actions, all of which are the practical value of the game. The game has a special importance in terms of physical and mental development of the child. The games influence the child's perceptual, sensory-motor activitie